THE INFLUENCE OF PERCEPTION AND EXPECTATION INTO CUSTOMER OVERALL SATISFACTION AND WORD OF MOUTH TO THE THAI FOOD DINING EXPERIENCE - Megawati Syahril (Universitas Islam Nahdlatul Ulama Jepara, 2014)
AbstractGlobally, there is a growing demand for food in a restaurant as a result of higher incomes, changes in consumption patterns and household composition, and the time pressures created by dual-working families. The trend is getting higher, especially in Yogyakarta. As the result, the foodservice industry in Yogyakarta has become highly competitive. Therefore, the number of food service outlets has been increasing to meet the demand. In order to succeed in this competitive industry, restaurant operators need to understand the factors (and the relative importance) that influence restaurant patrons?? decision when selecting a restaurant. Multiculturalism is an intrinsic part of the historical formation and development of the Indonesia, especially in Yogyakarta. The purpose of this study is to investigate: 1) customers' authentic expectation for food, as well as the overall experience 2) the amount of authenticity customers can accept in a future Thai restaurant experience and 3) what customers want from Thai restaurants to serve them when they are coming for the dining experience. To obtain the data, 150 questionnaires were distributed to guests in 2 Thai restaurants in Yogyakarta. AbstrakSecara global, terdapat peningkatan permintaan untuk makanan di restoran sebagai akibat dari peningkatan pendapatan, perubahan pola konsumsi dan komposisi rumah tangga, dan tekanan waktu yang dibuat oleh dual-working families. Kecenderungan tersebut semakin tinggi, khususnya di Yogyakarta. Akibatnya, industri jasa makanan di Yogyakarta menjadi sangat kompetitif. Oleh karena itu, jumlah outlet jasa makanan semakin meningkat untuk memenuhi permintaan. Dalam rangka mendukung keberhasilan dalam industri yang kompetitif ini, operator restoran perlu memahami faktor-faktor (dan relatif pentingnya) yang mempengaruhi keputusan pelanggan restoran 'ketika memilih sebuah restoran. Multikulturalisme merupakan bagian intrinsik dari pembentukan sejarah dan perkembangan Indonesia, khususnya di Yogyakarta. Tujuan dari penelitian ini adalah untuk mengetahui: 1) harapan pelanggan atas makanan yang tradisional, beserta pengalamannya 2) jumlah keauntetikan pelanggan yang dapat menerima restoran Thailand di masa mendatang dan 3) apa yang pelanggan harapkan dari restoran Thailand ketika mereka datang untuk menikmati hidangan. Data diperoleh dari 150 kuesioner yang dibagikan kepada pelanggan di 2 restoran Thailand di Yogyakarta.